Outcome of Intravenous Levetiracetam Versus Intravenous Phenytoin in Management of Children with Status Epilepticus" - Zaman, Saeed; Shuaib, Ayesha; Shah, Sajid Ali; Zahid, Muhammad; Khan, Qamar Uz Zaman; Murad, Masud (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the outcome of intravenous Levetiracetam versus intravenous Phenytoin in the management of children with status epilepticus Study Design: Quasi-experimental study. Place and Duration of Study: Department of Pediatric Medicine, Combined Military Hospital, Kharian, from Jan to Dec 2020. Methodology: Ninety children fulfilling the inclusion criteria were included in the study from emergency. Then patients were randomly divided into two groups by using the lottery method. In group A, patients were given Phenytoin (20 mg/kg) at presentation. In group B, patients were given Levetiracetam (20 mg/kg). These children were admitted to the pediatric ward and followed up until the resolution of symptoms. Duration of resolution of symptoms was noted. Then children were followed up further for 24 hours. If there was no recurrence of seizures, then it was noted. Results: The mean duration of resolution of symptoms in Group A and Group B was 22.24 ± 3.85 and 16.40 ± 4.50 seconds, respectively. No significant difference was seen in both treatment groups regarding recurrence, i.e., Group-A: 5 (11.1%) vs Group-B: 7 (15.6%), p-value=0.932. Conclusion: Based on the results of this study, it can be concluded that with Levetiracetam, the resolution of symptoms was faster than with Phenytoin. But recurrence rate showed no significant difference in children with status epilepticus.